Age‐dependent effects of diabetes and obesity on liver‐related events in non‐alcoholic fatty liver disease: Subanalysis of CLIONE in Asia. Issue 12 (19th October 2022) - Seko, Yuya; Kawanaka, Miwa; Fujii, Hideki; Iwaki, Michihiro; Hayashi, Hideki; Toyoda, Hidenori; Oeda, Satoshi; Hyogo, Hideyuki; Morishita, Asahiro; Munekage, Kensuke; Kawata, Kazuhito; Yamamura, Sakura; et al.
Abstract: Background and Aim: Older age, type 2 diabetes mellitus (T2DM), and obesity are known risk factors for liver‐related events (LREs). We investigated the impacts of T2DM and obesity on LRE according to age in Japanese patients with non‐alcoholic fatty liver disease (NAFLD). Methods: We performed a subanalysis of a retrospective cohort study (CLIONE in Asia), including 1395 patients with biopsy‐proven NAFLD. The median follow‐up was 4.6 years. Results: The median age was 57 years, and 36.2% had T2DM. The median body mass index (BMI) was 27.4, and 28.5% were severely obese (BMI ≥ 30). During follow‐up, 37 patients developed hepatocellular carcinoma (HCC), and 58 patients developed LRE. In patients younger than 65 years, advanced fibrosis (hazard ratio [HR] 7.69, P < 0.001) and T2DM (HR 3.37, P = 0.017) were HCC risk factors, and advanced fibrosis (HR 9.40, P < 0.001) and T2DM (HR 2.51, P = 0.016) were LRE risk factors. In patients 65 years and older, advanced fibrosis (HR 4.24, P = 0.010) and obesity (HR 4.60, P = 0.006) were HCC risk factors, and advanced fibrosis (HR 4.22, P = 0.002) and obesity (HR 4.22, P = 0.002) were LRE risk factors. Conclusion: Type 2 diabetes mellitus and obesity contributed to LRE in younger and older patients, respectively, along with advanced fibrosis. Therefore, controlling T2DM in patients younger than 65 years and controlling weight in patients 65 years and older could prevent LRE. The development of age‐dependent screening and management strategies is necessary for patients with NAFLD.